Three-dimensional geometrical changes of the human tibialis anterior muscle and its central aponeurosis measured with three-dimensional ultrasound during isometric contractions - Brent J. Raiteri; Andrew G. Cresswell; Glen A. Lichtwark (PeerJ, 2016)
Background. Muscles not only shorten during contraction to perform mechanical work, but they also bulge radially because of the isovolumetric constraint on muscle fibres. Muscle bulging may have important implications for muscle performance, however quantifying three-dimensional (3D) muscle shape changes in human muscle is problematic because of difficulties with sustaining contractions for the duration of an in vivo scan. Although two-dimensional ultrasound imaging is useful for measuring local muscle deformations, assumptions must be made about global muscle shape changes, which could lead to errors in fully understanding the mechanical behaviour of muscle and its surrounding connective tissues, such as aponeurosis. Therefore, the aims of this investigation were (a) to determine the intra-session reliability of a novel 3D ultrasound (3DUS) imaging method for measuring in vivo human muscle and aponeurosis deformations and (b) to examine how contraction intensity influences in vivo human muscle and aponeurosis strains during isometric contractions. Methods. Participants (n = 12) were seated in a reclined position with their left knee extended and ankle at 90° and performed isometric dorsiflexion contractions up to 50% of maximal voluntary contraction. 3DUS scans of the tibialis anterior (TA) muscle belly were performed during the contractions and at rest to assess muscle volume, muscle length, muscle cross-sectional area, muscle thickness and width, fascicle length and pennation angle, and central aponeurosis width and length. The 3DUS scan involved synchronous B-mode ultrasound imaging and 3D motion capture of the position and orientation of the ultrasound transducer, while successive cross-sectional slices were captured by sweeping the transducer along the muscle. Results. 3DUS was shown to be highly reliable across measures of muscle volume, muscle length, fascicle length and central aponeurosis length (ICC ≥ 0.98, CV < 1%). The TA remained isovolumetric across contraction conditions and progressively shortened along its line of action as contraction intensity increased. This caused the muscle to bulge centrally, predominantly in thickness, while muscle fascicles shortened and pennation angle increased as a function of contraction intensity. This resulted in central aponeurosis strains in both the transverse and longitudinal directions increasing with contraction intensity. Discussion. 3DUS is a reliable and viable method for quantifying multidirectional muscle and aponeurosis strains during isometric contractions within the same session. Contracting muscle fibres do work in directions along and orthogonal to the muscle’s line of action and central aponeurosis length and width appear to be a function of muscle fascicle shortening and transverse expansion of the muscle fibres, which is dependent on contraction intensity. How factors other than muscle force change the elastic mechanical behaviour of the aponeurosis requires further investigation.